Lichen spinulosus in a patient with Wilson’s disease. - Okan, G.; Vural, P.; Demirkesen, C. (European Journal of Pediatric Dermatology, 2025)
Lichen spinulosus (LS) is a rare dermatosis typically observed in children and young adults with unclear pathogenesis. Wilson’s disease (WD) is an autosomal recessive disorder characterized by pathological copper accumulation primarily in the liver, with subsequent effects on the other tissues. Oxidative stress resulting from increased free radical production along with deficiencies in antioxidant defence is believed to play a central role in WD pathogenesis. We report the a 12-year-old girl with WD whose symptoms were managed with beta-carotene and zinc rich supplements.